Laboratory evaluation of RealStar Yellow Fever Virus RT-PCR kit 1.0 for potential use in the global yellow fever laboratory network - Basile, Alison J.; Niedrig, Matthias; Lambert, Amy J.; Meurant, Robyn; Brault, Aaron C.; Domingo, Cristina; Goodman, Christin H.; Johnson, Barbara W.; Mossel, Eric C.; Mulders, Mick N.; Velez, Jason O.; Hughes, Holly R. (PLoS neglected tropical diseases, 2022)
Early detection of human yellow fever (YF) infection in YF-endemic regions is critical to timely outbreak mitigation. African National Laboratories chiefly rely on serological assays that require confirmation at Regional Reference Laboratories, thus delaying results, which themselves are not always definitive often due to antibody cross-reactivity. A positive molecular test result is confirmatory for YF; therefore, a standardized YF molecular assay would facilitate immediate confirmation at National Laboratories. The WHO-coordinated global Eliminate Yellow Fever Epidemics Laboratory Technical Working Group sought to independently evaluate the quality and performance of commercial YF molecular assays relevant to use in countries with endemic YF, in the absence of stringent premarket assessments. This report details a limited laboratory WHO-coordinated evaluation of the altona Diagnostics RealStar Yellow Fever Virus RT-PCR kit 1.0. Specific objectives were to assess the assay's ability to detect YF virus strains in human serum from YF-endemic regions, determine the potential for interference and cross-reactions, verify the performance claims as stated by the manufacturer, and assess usability. RNA extracted from normal human serum spiked with YF virus showed the assay to be precise with minimal lot-to-lot variation. The 95% limit of detection calculated was approximately 1,245 RNA copies/ml [95% confidence interval 497 to 1,640 copies/ml]. Positive results were obtained with spatially and temporally diverse YF strains. The assay was specific for YF virus, was not subject to endogenous or exogenous interferents, and was clinically sensitive and specific. A review of operational characteristics revealed that a positivity cutoff was not defined in the instructions for use, but otherwise the assay was user-friendly. The RealStar Yellow Fever Virus RT-PCR kit 1.0 has performance characteristics consistent with the manufacturer's claims and is suitable for use in YF-endemic regions. Its use is expected to decrease YF outbreak detection times and be instrumental in saving lives.